PEMBERIAN ASI EKSKLUSIF BERPENGARUH TERHADAP PERKEMBANGAN MOTORIK BAYI USIA 3-6 BULAN DI PUSKESMAS II DENPASAR BARAT - Putri, Ni Made Nuryastiwi; Widnyana, Made; Putra, I Putu Yudi Pramana; Saraswati, Ni Luh Putu Gita Karunia (Majalah Ilmiah Fisioterapi Indonesia; Vol 11 No 2 (2023): Majalah Ilmiah Fisioterapi Indonesia, 2023)
Background: Every newborn baby will experience a process of growth and development as they get older. Growth and development that involves the ability of muscles and nerves, namely motor development which is trained as early as possible to prevent delays. In addition to being given stimulation to support motor development, it is important to pay attention to the nutrition provided. Exclusive breastfeeding until the age of 6 months can prevent delays in motor development in children. This study aims to determine whether exclusive breastfeeding has an effect on motor development of infants aged 3-6 months in Banjar Sumuh, Puskesmas II Denpasar Barat. Methods: This research is a cross sectional study with the sampling technique used is total sampling. The number of samples in this study were 34 samples that had been determined through inclusion, exclusion and drop out criteria. Data was collected by conducting interviews with the sample mothers regarding breastfeeding status and measuring the motor development of the sample using the DDST/Denver II questionnaire. Results: Based on the non-parametric chi square analysis test, the value of p=0,04 (p<0.05). Conclusions: Based on the results of the study, it can be concluded that there is a relationship between exclusive breastfeeding and the motor development of infants aged 3-6 months in Banjar Sumuh, Puskesmas II Denpasar Barat. Keywords: exclusive breastfeeding, motor development, baby